Family climate influences next-generation family business leader effectiveness and work engagement - Miller, Stephen P. (Frontiers in Psychology, 2023)
Effective next-generation leadership is central to the multi-generational survival of family businesses. This study of 100 next-generation family business leaders found that business-owning families that openly express their opinions, take time to listen to each other, and squarely address difficult issues positively influence the development of the emotional and social intelligence competencies in next-generation family leaders that drive their leadership effectiveness. That kind of open and transparent communication in the family also makes it more likely next-generation leaders will be held accountable for their leadership performance by others, which increases the degree to which they are positively engaged with their work in the family firm. On the other hand, the results suggest that senior-generation family leaders who lead autocratically, a leadership style often observed in entrepreneurs who found family firms, make it less likely that next-generation family leaders will learn the emotional and social intelligence competencies that predict their leadership effectiveness. The study also found that autocratic senior-generation leaders negatively affect next-generation leader self-efficacy and make it less likely that others will hold them accountable, which limits their engagement with work in the family business. One of the study’s most important findings is that next-generation leader acceptance of personal responsibility for their leadership behaviors and results serves as a mediator through which the nature of the family climate influences their leadership effectiveness and work engagement. This suggests that while the nature of family relationships may make it easier or more difficult, next-generation family leaders have ultimate control over the development of their leadership talent and the inspiration, enthusiasm, energy, and pride they feel when working in the family business.